Effects of a single dose of a betalain-rich concentrate on determinants of running performance and recovery muscle blood flow: a randomized, triple-blind, placebo-controlled, crossover trial - Steven Vitti; Michael Bruneau; Leah Bisgrove; Samuel Grey; Sarah Levine; Craig Mattern; Justin Faller (European Journal of Applied Physiology, 2025)
Purpose This study aimed to examine the effects of a single dose of a betalain-rich concentrate (BRC) on determinants of running performance and recovery lactate clearance. Methods In this a randomized, triple-blind, placebo-controlled, crossover trial, 17 male recreational runners (Age: 19.0 ± 1.0 years; Height: 176.8 ± 6.2 cm; Weight: 70.62 ± 8.1 kg; Body fat: 12.8 ± 0.03%; VO 2max : 58.9 ± 8.6 ml/kg/min) consumed an acute dose of a BRC (100 mg) or a placebo (100 mg of dextrose; CON) and performed a running economy protocol (RE) at velocities corresponding to 60% and 80% of maximal oxygen consumption (VO 2max ) followed by a VO 2max test. Both exercise and recovery skeletal muscle oxygenation (SmO 2 ) were assessed via near-infrared spectroscopy (NIRS), and recovery lactate was obtained. Results BRC resulted in lower heart rate (HR) at velocities corresponding to 80% of VO 2max ( p = 0.05) and maximum HR (HR max ; p = 0.01), and a lower rating of perceived exertion (RPE) at velocities corresponding to 60% of VO 2max ( p = 0.02) when compared to CON. BRC also improved post-exercise SmO 2 at 3 ( p = 0.05), 4 ( p = 0.02), and 5 min ( p = 0.01) but not lactate clearance ( p > 0.05). BRC did not significantly improve RE or VO 2max ( p > 0.05). Conclusions A single dose of BRC did not enhance RE or VO 2max . However, the observed improvements in exercise HR, RPE, and SmO₂ suggest that BRC may confer cardiovascular benefits for exercise and recovery.

Targeting the Ubiquitin E3 Ligase MuRF1 to Inhibit Muscle Atrophy - Michael J. Eddins; Jeffrey G. Marblestone; K. G. Suresh Kumar; Craig A. Leach; David E. Sterner; Michael R. Mattern; Benjamin Nicholson (Cell Biochemistry and Biophysics, 2011)